Integrating Circular Economy and Sustainable Innovation to Drive Value in Ergo-Iconic Agricultural Products - Andriyansah; Fatimah, Fatia; Hermajiwandini, Chandra Murti Dewi Widowati; Nurhayati, Suci; Graciafernandy, Maria Augustine; Nurdiyah (Yayasan Sinergi Kawula Muda, 2026)
The circular economy (CE) has moved to the center of sustainability-driven innovation, with agriculture playing a pivotal role due to its large biomass flows and potential for resource optimization. This study investigates how CE practices relate to sustainable innovation, specifically highlighting value creation for “ergo-iconic” agricultural products—goods that uniquely combine ergonomic functionality (usability, durability, and human-centered design) with culturally embedded, sustainability-oriented identity attributes (place-based branding, heritage value, and symbolic meaning). Employing a qualitative exploratory design in Banten, Indonesia, we conducted semi-structured interviews with ten key informants comprising five agro-industry practitioners, three industry analysts, and two NGO representatives. We complemented this primary data with rigorous document analysis to ensure a holistic understanding of the context. Thematic analysis and triangulation were employed to establish the credibility of the findings. The results indicate that circular business models not only reduce waste but also serve as catalysts for broader innovation processes. Three primary drivers consistently emerged: (1) stakeholder engagement, (2) cross-sector collaboration, and (3) the adoption of environmentally friendly technologies. Building on these insights, we propose the CircAgriResilient Nexus (CAR-Nexus)—a comprehensive framework that conceptualizes circularity as a dynamic nexus connecting four pillars: Circularity, Agri-Innovation, Resilience, and Nexus Governance. CAR-Nexus differs from existing sustainable circular bioeconomy models by explicitly positioning resilience as a core system capability and by integrating a provisional Resilience Index Score (RIS)—a conceptual tool that synthesizes resource efficiency, social progress, and economic robustness to guide balanced assessment of circular transitions. This framework clarifies how circular resource flows, eco-innovation, and inclusive governance jointly enhance market, environmental, and social value within the Industry 4.0 era. The study contributes theoretically by articulating an integrative CE-innovation-resilience nexus tailored specifically to agri-food systems, and practically by outlining actionable levers for firms and policymakers to accelerate circular transitions in developing economies.